(untitled) (CIPEEX, 2025)
Colorectal cancer (CRC) remains one of the leading causes of cancer related morbidity and mortality worldwide, with rising incidence in younger populations and significant impact on healthcare systems. Its development follows a multistep process involving genetic alterations, epigenetic modifications, and environmental factors that promote progression from adenoma to carcinoma. The aim of this study was to review current strategies for screening, diagnosis, and treatment of CRC, with emphasis on advances that have improved prognosis. A literature search was conducted in PubMed, Scielo, and Embase databases, focusing on clinical guidelines, randomized controlled trials, and systematic reviews published within the last decade. The results demonstrated that early detection through colonoscopy remains the gold standard for screening, enabling removal of precancerous lesions and reducing mortality. Alternative methods, including fecal immunochemical testing and multitarget stool DNA assays, have increased accessibility, especially in populations with limited colonoscopy availability. Regarding treatment, surgical resection remains the cornerstone of localized disease, complemented by neoadjuvant and adjuvant chemotherapy in selected cases. For advanced CRC, molecular profiling has guided the use of targeted therapies, including anti-EGFR and anti-VEGF monoclonal antibodies, as well as immune checkpoint inhibitors in microsatellite instability-high tumors. These advances have prolonged survival and improved quality of life, though challenges persist regarding drug resistance, toxicity, and unequal access to innovative therapies. In addition, lifestyle modifications and preventive strategies, such as dietary interventions and physical activity, play an essential role in reducing incidence. In conclusion, CRC management has evolved from a one-size-fits-all approach to precision medicine, integrating early detection, minimally invasive surgery, personalized systemic therapy, and supportive care. Continued efforts in population-based screening programs and translational research are crucial to reduce disease burden and further improve patient outcomes.